2015
DOI: 10.1104/pp.15.00021
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Responsive CONSTANS, CONSTANS-Like, and Time of Chlorophyll a/b Binding Protein Expression1 Protein Is a Positive Regulator of Starch Synthesis in Vegetative Organs of Rice

Abstract: A unique CO 2 -Responsive CONSTANS, CONSTANS-like, and Time of Chlorophyll a/b Binding Protein1 (CCT) Protein (CRCT) containing a CCT domain but not a zinc finger motif is described, which is up-regulated under elevated CO 2 in rice (Oryza sativa). The expression of CRCT showed diurnal oscillation peaked at the end of the light period and was also increased by sugars such as glucose and sucrose. Promoter b-glucuronidase analysis showed that CRCT was highly expressed in the phloem of various tissues such as lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 50 publications
7
58
3
Order By: Relevance
“…Although we found many genes that were expressed differently between TS and KH ( Figure 5), these genes are not necessarily responsible for high sugar accumulation in TS because the observed differences in expression levels might result from the differences in sugar concentration between TS and KH. For example, CRCT (CO 2 -responsive CCT protein; Os05g0595300) is a transcription factor that regulates the expression of genes related to starch metabolism such as AGPL1, BE1, and Pho1 in rice stem, and its expression is known to be up-regulated by sugars, especially sucrose (Morita et al, 2015). Consistent with the findings, the expression level of CRCT was 1.8 times higher in TS than KH (Supplemental Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…Although we found many genes that were expressed differently between TS and KH ( Figure 5), these genes are not necessarily responsible for high sugar accumulation in TS because the observed differences in expression levels might result from the differences in sugar concentration between TS and KH. For example, CRCT (CO 2 -responsive CCT protein; Os05g0595300) is a transcription factor that regulates the expression of genes related to starch metabolism such as AGPL1, BE1, and Pho1 in rice stem, and its expression is known to be up-regulated by sugars, especially sucrose (Morita et al, 2015). Consistent with the findings, the expression level of CRCT was 1.8 times higher in TS than KH (Supplemental Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, the composition of rice straws of CRCT transgenic lines was analyzed (Table 1). As expected from the results of Morita et al (2015), the starch contents of CRCT overexpression lines were greatly increased compared with that of non-transgenic rice. In (2013) reported that glucose contents in liquid hydrolyzate of rice straw was varied depending on cultivars and ranged from 5.0 to 24.5 g per 100 g DW among 13 rice cultivars in Japan.…”
Section: Effects Of Crct Expression Levels On Glucose Content In Liqusupporting
confidence: 67%
“…This defect in yield should be improved and can be overcome by the modification of genetic engineering. In our transgenic line, CRCT was overexpressed using the actin promoter which provides high levels of constitutive expression (Morita et al, 2015). The constitutive enhancement of starch synthesis could reduce the partitioning of photoassimilates to the reproductive organ when needed for its development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations